PENGARUH SUBSTITUSI TEPUNG KACANG TUNGGAK Vigna unguiculata L. DAN TEPUNG KACANG HIJAU Vigna radhiata TERHADAP MUTU KIMIA, MUTU GIZI, DAN MUTU ORGANOLEPTIK BISKUIT SEBAGAI PMT IBU HAMIL KEK - Oktavia, Deby Prestia Indah; Razak, Maryam; Pudjirahaju, Astutik (Poltekkes Kemenkes Malang, 2022)
The prevalence of CED in pregnant women in 2013 was 24.2Percent nationally and decreased to 17.3Percent in 2018. Despite the decline, the prevalence is still relatively high compared to the target of the Policy Direction and Action Plan for the Public Health Program for 2020 until 2024, namely 10Percent. One of the countermeasures for pregnant women with CED is the provision of additional food made from flour that was imported. Local food diversification is needed to reduce dependence on imported food. Cowpea flour and green beans have high protein and iron levels. However, in this case cowpeas are not favored from the sensory properties of the taste, namely bitter. Meanwhile, green beans have a good sensory that is savory and nutty. to analyze the effect of substitution of cowpea flour and mung bean flour on the chemical quality, nutritional quality, and organoleptic quality of biscuits as PMT for pregnant women with CED. This type of research is experimental with a completely randomized design CRD. The higher the proportion of cowpeas, the higher the levels of protein, fat, and vitamin C. While the higher the proportion of mung bean flour, the higher the carbohydrate, iron, and energy values. The higher the proportion of cowpea flour, the lower the preference for organoleptic quality and the higher the proportion of mung bean flour, the higher the preference for organoleptic quality. Substitution of cowpea flour and mung bean flour had a significant effect on the panelists preference for color and texture. The substitution of cowpea flour and mung bean flour has a significant effect on the chemical quality and nutritional quality of biscuits. Treatment level P3 is the besttreatmentlevel.